(untitled) (Jurnal Komunikasi Pembangunan, 2017)
This study aims to formulate a communication model to build the readiness of changes in traditional market traders. This research is related to traditional market revitalization plan to face competition especially from modern retailer. The method used is survey which result is analyzed by using causality approach with LISREL tool and reinforced with result from depth interview. The result is in the picture that in the face of revitalization, traders are in a situation of uncertainty. On the other hand, overall elements ranging from trader characteristics, message sources, messages, and participatory communications have a positive impact on merchant readiness associated with revitalization with high-capacity merchant corporation conditions. However, to build the readiness of traders, the main thing to do is to build the entrepreneurial capacity of traders. The lack of success in building entrepreneurial capacity has a negative impact on the readiness of traders. Appropriate communication models involving market managers as a credible source of messages, message content on the benefits and risks of effective revitalization develop the trader’s motivation to change, and the media that permits immediate responses from communication actors.